A efetividade da punição nos crimes de Violência contra a mulher - um olhar sobre o juizado especial criminal de Campina Grande-PB - - Barbosa, Ghislaine Alves (2006)
In spite of the progresses that happened along the social history (in Brazil specifically with the Federal Constitution of 1988), they last long in the days current rests of a culture of inequalities. In this context, the violence against the woman (physics, sexual and psychological), it assumes frightening proportions. Even with the implement of some public politics, as the Specialized Police stations in the attendance to the women, statistics demonstrate that the cases of violence against the woman and consequent impunity are growing. Such crimes are covered of peculiarities, as the subordination relationship among perpetrator/victim, and of this factor it elapses the fear of denouncing. It is also believed that the subject of the punishment is shown as important factor in this point, because when seeing your aggressor to render services to the community or to donate basic baskets as feather, by virtue of the institute of the "penal transaction", allowed in the Brazilian juridical order, the women are humiliated. Our research looked for to study the cases of women's aggression that process in the ambit of Criminal Special Court of Campina Grande - PB, analyzing the penalty imposed the aggressor in your legal aspects. It is noticed that most of the processes originating from of the Police Station of the Women that processed in Court was concluded with the victim's "cessation ", for the peculiarity of the crime and your circumstances and that we too much there was penal transaction. With the results of the research, it intends to contribute for the development of public politics and legislative reforms that are really effective in the woman's defense.